Implementasi Pengendalian Persediaan dan Dampaknya terhadap Tata Kelola Persediaan Barang Dagangan - Bakri Bakri (Al-Buhuts, 2020)
This study aims to determine and analyze how much influence the Inventory Internal Control System Against the Fairness of the Management of Merchandise Inventory at PT. Magnificent Columbus Bumi Sulawesi Gorontalo Branch. In this study the authors chose the type of quantitative research, using survey methods, and using questionnaires as a primary data collection tool and using the path analysis method as a data analysis method. The results showed that the internal control system of supply (X) simultaneously had a positive and significant effect on the fairness of managing merchandise inventory (Y) at PT. Columbus Magnificent Bumi Sulawesi Gorontalo Branch of 0.694 or 69.4%. there are 0.693 or 69.3% which is influenced by external variables that are not examined, storage and physical supervision (X1) of 0.354 or 35.4%, Inventory accounting (X2) of 0.227 or 22.7%, Costing system ( X3) as much as 0.362 or 36.2% which has a partial effect on the fairness of managing merchandise inventory (Y). and there are other variables